RealityMedia: immersive technology and narrative space - Jang, So-Youn; Park, Jisu; Engberg, Maria; MacIntyre, Blair; Bolter, Jay D. (Frontiers in Virtual Reality, 2023)
In this paper, we treat VR as a new writing space in the long tradition of inscription. Constructing Virtual Reality (VR) narratives can then be understood as a process of inscribing text in space, and consuming them as a process of “reading” the space. Our study focuses on providing a deeper context for designing VR narratives by exploiting the immersive space as affording a new kind of book. We argue that, as opposed to the linear space of a printed book, a VR narrative space is similar to the physical space of a museum and can be analyzed on three distinct levels: (1) the architecture of the space itself, (2) the collection, and (3) the individual artifacts. We designed and implemented a testbed called RealityMedia to explore digital remediations of traditional narrative devices and the spatial, immersive, and interactive affordances of VR. Our research objective is to explore the meaning-making process afforded by spatial narratives—to test whether VR facilitates traditional ways of weaving complex, multiple narrative strands and provides new opportunities for leveraging space. To accomplish this, we conducted task-based user study using a VR headset and follow-up qualitative interviews with 20 participants. Our results highlight how the three semantic levels (space, collection, and artifacts) can work together to constitute meaningful narrative experiences in VR.